A multi-institutional study of perioperative and functional outcomes for pediatric robotic-assisted laparoscopic Mitrofanoff appendicovesicostomy. Issue 6 (December 2016) - Gundeti, Mohan S.; Petravick, Michael E.; Pariser, Joseph J.; Pearce, Shane M.; Anderson, Blake B.; Grimsby, Gwen M.; Akhavan, Ardavan; Dangle, Pankaj P.; Shukla, Aseem R.; Lendvay, Thomas S.; Cannon, Glenn M.; Gargollo, Patricio C.
Summary: Background: Robotic techniques are increasingly being used for reconstructive procedures in the pediatric population. Objective: The present study reported the functional and perioperative outcomes of a multi-institutional cohort of pediatric patients who underwent robotic-assisted laparoscopic Mitrofanoff appendicovesicostomy (RALMA). Study design: Pediatric patients who underwent RALMA at five different centers were included. Positioning is shown (Summary Figure ). Demographics were gathered, and intraoperative parameters included concomitant procedures, detrusor tunnel length, estimated blood loss (EBL) and operative time. Perioperative outcomes included length of hospital stay (LOS), morphine use and 30-day complications. Outcomes were reported in terms of stomal continence and surgical revisions. Results: Eighty-eight patients with a mean age of 10.4 ± 4.0 years were included in the analysis. Median follow-up was 29.5 months (IQR 11.8–45.0). Bladder augmentation was performed concomitantly in 15 (17%) patients, and bladder neck procedures in 34 (39%). Mean detrusor tunnel length was 3.9 ± 1.0 cm, EBL was 54 ± 70 ml, and operative time was 424 ± 120 min. Postoperatively, mean LOS was 5.2 ± 2.8 days. Patients who underwent concomitant augmentation had higher EBL and operative times (both P < 0.05). At 90 days, complications occurred in 26 patients (29.5%) with six Clavien grade ≥3 (6.8%). During follow-up, 11 (12.5%) patients required appendicovesicostomy revision. Regarding functional outcomes, 75 (85.2%) patients were initially continent. After additional procedures, 81 (92.0%) patients were continent at last follow-up. Discussion: Compared to previous open series, initial stomal continence rates with RALMA were acceptable, with a minority of patients requiring subsequent procedures to manage complications and achieve continence. Conclusion: RALMA is safe and effective in a pediatric population with regard to perioperative complications and stomal continence. Summary Figure Adapted from Chang et al. with permission[1] .